¿Contribuyen las reservas comunitarias de semillas a la resiliencia socio-ecológica? – un caso de estudio en la Sierra de los Cuchumatanes, Guatemala - Procuna Ferrer, A.; Asociación de Organizaciones de los Cuchumatanes; Bioversity International (2018)
A community seed bank is a locally governed and managed, mostly informal institution whose core function is to maintain seeds for local use, strengthen local seed systems and support on-farm agrobiodiversity conservation. The objective of this study was to explore, from a farmer’s perspective, if and how community seed banks are supporting change towards a more resilient socio-ecological system. The research used a participatory case study approach and the methodology combined tools of participatory research and standard qualitative methods. Theories of socio-ecological resilience are used for the analysis of change. Field work was conducted between March and July 2017 in the Sierra de los Cuchumatanes, Guatemala, in collaboration with Bioversity International and ASOCUCH, a Guatemalan association of agricultural cooperatives. Financial support was provided by the Seeds, Soil and Culture Fund of RSF Social Finance, a programme managed by the New Field Foundation. The research contributes to the CGIAR program on Policies, Institutions and Markets led by IFPRI. The research will be used to write a Master thesis to complete the study program in Organic Farming Systems and Agroecology at the University of Natural Resources and Life Sciences of Vienna (BOKU).